2011
DOI: 10.1002/hyp.8348
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of hydrological variables to climate change in the Haihe River basin, China

Abstract: Abstract:Using the defined sensitivity index, the sensitivity of streamflow, evapotranspiration and soil moisture to climate change was investigated in four catchments in the Haihe River basin. Climate change contained three parts: annual precipitation and temperature change and the change of the percentage of precipitation in the flood season (P f ). With satisfying monthly streamflow simulation using the variable infiltration capacity model, the sensitivity was estimated by the change of simulated hydrologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 48 publications
(67 reference statements)
1
29
0
1
Order By: Relevance
“…Wang et al (2013a, b) concluded that an increase in precipitation in the Kuye River catchment on the Loess Plateau of China is leading to greater changes in runoff than a decrease in precipitation of the same magnitude. Bao et al (2012) found that climate change has a larger impact on Hai River stream flow than its impacts on evapotranspiration or soil moisture. Stream flows in most humid or arid areas are more sensitive to changes in precipitation than to change in temperature (Zhang and Wang 2007;Fu et al 2007;Bao et al 2012).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Wang et al (2013a, b) concluded that an increase in precipitation in the Kuye River catchment on the Loess Plateau of China is leading to greater changes in runoff than a decrease in precipitation of the same magnitude. Bao et al (2012) found that climate change has a larger impact on Hai River stream flow than its impacts on evapotranspiration or soil moisture. Stream flows in most humid or arid areas are more sensitive to changes in precipitation than to change in temperature (Zhang and Wang 2007;Fu et al 2007;Bao et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Bao et al (2012) found that climate change has a larger impact on Hai River stream flow than its impacts on evapotranspiration or soil moisture. Stream flows in most humid or arid areas are more sensitive to changes in precipitation than to change in temperature (Zhang and Wang 2007;Fu et al 2007;Bao et al 2012). Changes in runoff are normally one to three times greater than changes in precipitation (IPCC 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The hydroclimatic variables analyzed generally include precipitation amount, surface air temperature, evapotranspiration, and streamflow [8][9][10][11][12]. The previous precipitation studies have focused mainly on changes in annual or monthly precipitation amounts and have ignored changes in precipitation structure including precipitation amount, mean precipitation intensity, and precipitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some studies related to trend analysis of hydroclimatic variables at watershed scale have been carried out, for example in the Lake Victoria Basin in East Africa [5], the Yellow River Basin [6], and the Three Gorges Reservoir [7]. The hydroclimatic variables analyzed generally include precipitation amount, surface air temperature, evapotranspiration, and streamflow [8][9][10][11][12]. The previous precipitation studies have focused mainly on changes in annual or monthly precipitation amounts and have ignored changes in precipitation structure including precipitation amount, mean precipitation intensity, and precipitation frequency.…”
Section: Introductionmentioning
confidence: 99%